The Effect of Restructuring and Organizational Commitment on Employee Performance in BPS-Statistics of Kepulauan Bangka Belitung Province - Livio Mayesta; Obed Bida; Darmanto Darmanto (Department of Public Administration, Muhammadiyah University of Makassar, 2022)
This study aims to analyze the effect of restructuring and organizational commitment on employee performance in BPS-Statistics of Kepulauan Bangka Belitung Province. To measure organizational restructuring, Melcher's theory is used which consists of the dimensions of workflow, task complexity, formal authority, formal control, and communication systems. Meyer Allen's theory is used to measure commitment, namely affective commitment, continuance commitment, and normative commitment. Meanwhile, to measure performance, Husnan's theory is used, namely the quality of work, the quantity of work, level of reliability, and attitude. The research design used in this study is a causal quantitative research design. Objects that are used as respondents in this study are employees in BPS-Statistics of Kepulauan Bangka Belitung Province with a total of 55 people. The analytical tools used include descriptive analysis, classic assumption test, hypothesis testing, regression analysis, and coefficient of determination. The results of this study conclude that Restructuring and organizational commitment have a positive and significant effect on employee performance in BPS-Statistics of Kepulauan Bangka Belitung Province by 56.3 percent.